2018
DOI: 10.1038/s41422-018-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-mediated N6-methyladenosine mRNA modification enhances long-term memory consolidation

Abstract: The formation of long-term memory is critical for learning ability and social behaviors of humans and animals, yet its underlying mechanisms are largely unknown. We found that the efficacy of hippocampus-dependent memory consolidation is regulated by METTL3, an RNA N6-methyladenosine (m6A) methyltransferase, through promoting the translation of neuronal early-response genes. Such effect is exquisitely dependent on the m6A methyltransferase function of METTL3. Depleting METTL3 in mouse hippocampus reduces memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
200
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(208 citation statements)
references
References 33 publications
7
200
0
1
Order By: Relevance
“…Recent studies have highlighted neuronal functions of mammalian m 6 A pathway factors (Du et al, 2019;Widagdo and Anggono, 2018). There is a growing appreciation that mouse mutants of multiple components in the m 6 A RNA-modification machinery affect learning and memory (Koranda et al, 2018;Walters et al, 2017;Widagdo et al, 2016;Zhang et al, 2018c). Here, we provide substantial evidence that, in Drosophila, neural m 6 A is critical for short-term memory (STM).…”
Section: Roles For the M 6 A/df1 Pathway In Learning And Memorymentioning
confidence: 61%
See 2 more Smart Citations
“…Recent studies have highlighted neuronal functions of mammalian m 6 A pathway factors (Du et al, 2019;Widagdo and Anggono, 2018). There is a growing appreciation that mouse mutants of multiple components in the m 6 A RNA-modification machinery affect learning and memory (Koranda et al, 2018;Walters et al, 2017;Widagdo et al, 2016;Zhang et al, 2018c). Here, we provide substantial evidence that, in Drosophila, neural m 6 A is critical for short-term memory (STM).…”
Section: Roles For the M 6 A/df1 Pathway In Learning And Memorymentioning
confidence: 61%
“…Recent studies showed that m 6 A pathway is required for learning and memory in mice Zhang et al, 2018c). We used a classical aversive conditioning paradigm to test Drosophila m 6 A mutants for deficits in short-term memory (henceforth 'STM' or 'memory').…”
Section: Neural Autonomous Function Of M 6 a Supports Olfactory Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mRNA transcript stability and translation was shown to critically depend on N 6 -methyladenosine (m 6 A) modification 6-8 , a process bidirectionally regulated upon learning by the m 6 A methylase METTL3 and the demethylase FTO [6][7][8] . In the current study, Zhang et al 2 investigated whether m 6 A modification of mRNA might influence translation of IEGs and memory strength. The authors knocked out METTL3 in postnatal forebrain, including hippocampus, using mice expressing a conditional allele of METTL3 in a CaMK2-Cre background.…”
mentioning
confidence: 93%
“…To overcome these challenges, there has been a need for identification of relevant endogenous molecular processes that modulate memory strength after acquisition. The paper by Zhang et al 2 makes an important contribution towards this objective.…”
mentioning
confidence: 99%